2022
DOI: 10.1083/jcb.202202011
|View full text |Cite
|
Sign up to set email alerts
|

The low-density lipoprotein receptor–mTORC1 axis coordinates CD8+ T cell activation

Abstract: Activation of T cells relies on the availability of intracellular cholesterol for an effective response after stimulation. We investigated the contribution of cholesterol derived from extracellular uptake by the low-density lipoprotein (LDL) receptor in the immunometabolic response of T cells. By combining proteomics, gene expression profiling, and immunophenotyping, we described a unique role for cholesterol provided by the LDLR pathway in CD8+ T cell activation. mRNA and protein expression of LDLR was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Whether a similar mechanism exists in T cells remains unclear, as variable results have been reported between the correlation of cholesterol levels and mTORC1 activation. In support of this mechanism, deletion of LDLR in CD8 T cells was associated with decreased cholesterol at the lysosome and lower mTORC1 activation 169 . In other studies, the adding MβCD cholesterol to SCAP‐deficient and HDAC‐deficient T cells rescues proliferation without altering mTORC1 signaling, suggesting that alternative mechanisms exist to couple intracellular cholesterol with T cell growth and metabolism 1,164 .…”
Section: Coordinated Regulation Of the Mva Pathway Regulates T Cell F...mentioning
confidence: 85%
See 3 more Smart Citations
“…Whether a similar mechanism exists in T cells remains unclear, as variable results have been reported between the correlation of cholesterol levels and mTORC1 activation. In support of this mechanism, deletion of LDLR in CD8 T cells was associated with decreased cholesterol at the lysosome and lower mTORC1 activation 169 . In other studies, the adding MβCD cholesterol to SCAP‐deficient and HDAC‐deficient T cells rescues proliferation without altering mTORC1 signaling, suggesting that alternative mechanisms exist to couple intracellular cholesterol with T cell growth and metabolism 1,164 .…”
Section: Coordinated Regulation Of the Mva Pathway Regulates T Cell F...mentioning
confidence: 85%
“…In support of this mechanism, deletion of LDLR in CD8 T cells was associated with decreased cholesterol at the lysosome and lower mTORC1 activation. 169 In other studies, the adding MβCD cholesterol to SCAP-deficient and HDAC-deficient T cells rescues proliferation without altering mTORC1 signaling, suggesting that alternative mechanisms exist to couple intracellular cholesterol with T cell growth and metabolism. 1,164 Loss of ABCG1 causes an accumulation of cholesterol; however, studies also found decreased mTORC1 signaling.…”
Section: Bioenergetic Metabolismmentioning
confidence: 90%
See 2 more Smart Citations
“…A total of 10 μg of proteins was completely dried in a vacuum concentrator at 45 °C for 45 min. Afterward, the dried protein pellet was resuspended in 10 μL of water plus 10 μL of 50 mM ammonium bicarbonate solution (final pH 8.5), followed by protein reduction with 5 mM DTT for 20 min at 55 °C, as previously described. , Proteins were then alkylated at room temperature by incubation with 15 mM iodoacetamide for 30 min in the dark. Trypsin (#T7575-1KT, Merck Millipore, Billerica, MA) digestion with a 1:20 enzyme/protein ratio was performed overnight at 37 °C and terminated by acidification with trifluoroacetic acid (final concentration 1%).…”
Section: Experimental Proceduresmentioning
confidence: 99%